Internet-delivered Parent-Child Interaction Therapy (I-PCIT) in Japan: Case Report of Application to a Maltreating Parent-Child Dyad - Kawasaki, Masako; Kamo, Toshiko (Archives of Clinical and Medical Case Reports, 2020)
Internet-delivered Parent-Child Interaction Therapy (I-PCIT) follows traditional clinic-based PCIT but uses a videoconferencing software to allow therapists to provide therapy remotely to families in their homes. We report the I-PCIT course of treatment for a 4-year-old Japanese boy (K) and his parents, an abusive parent-child dyad. This is the first report examining the applicability of I-PCIT in Japan. Weekly sessions were held for 60-90 minutes. At the end of the treatment, K showed a significant decrease in problematic behaviors, such as screaming, throwing objects, and hitting his parents. I-PCIT may be effective in helping both children and parents of families at high risk of abuse. In addition, parents’ skills are more likely to be generalized because the I-PCIT sessions are held at a site where problematic behaviors usually occur. I-PCIT is also useful for training new therapists; and with the growing need for specific abuse prevention initiatives that can be implemented remotely during the ongoing coronavirus pandemic, the benefits of the widespread use of I-PCIT are invaluable.